2017
DOI: 10.1115/1.4037036
|View full text |Cite
|
Sign up to set email alerts
|

Forcing Boundary-Layer Transition on a Single-Element Wing in Ground Effect

Abstract: The transition from a laminar to turbulent boundary layer on a wing operating at low Reynolds numbers can have a large effect on its aerodynamic performance. For a wing operating in ground effect, where very low pressures and large pressure gradients are common, the effect is even greater. A study was conducted into the effect of forcing boundary-layer transition on the suction surface of an inverted GA(W)-1 section single-element wing in ground effect, which is representative of a racing-car front wing. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…For the latter, the fully turbulent boundary layer which forms from the leading edge of the model means that no laminar separation occurs, and thus the bubble does not form, and instead turbulent separation occurs close to the trailing edge. 11 The important difference, therefore, is that the k-k L -ω model allows a laminar separation to occur, while the k-ω SST model only contains turbulent separations. The difference between such separation phenomena is that a turbulent boundary layer is more resilient to the adverse pressure gradient, due to fluctuating velocity components providing momentum transfer normal to the surface, and thus separation occurs at a more downstream location.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the latter, the fully turbulent boundary layer which forms from the leading edge of the model means that no laminar separation occurs, and thus the bubble does not form, and instead turbulent separation occurs close to the trailing edge. 11 The important difference, therefore, is that the k-k L -ω model allows a laminar separation to occur, while the k-ω SST model only contains turbulent separations. The difference between such separation phenomena is that a turbulent boundary layer is more resilient to the adverse pressure gradient, due to fluctuating velocity components providing momentum transfer normal to the surface, and thus separation occurs at a more downstream location.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the separation bubble to be a force-enhancement mechanism as it alters the effective shape of the wing to give it more effective camber; this helps to maintain suction levels and increase circulation. 10,11 It is the increase in circulation that causes suction across the entire lower surface to be increased. In addition to altering the aerodynamic forces that the wing generates, changes to the pressure field on a three-dimensional wing can also affect the formation of wing-tip vortices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations